Inside job - Damon, Matt (Sony Pictures Classics, 2010)
Provides an analysis of the global financial crisis of 2008. At a cost of over $20 trillion, it caused millions of people to lose their jobs and homes in the worst recession since the Great Depression and nearly resulted in a global financial collapse. Through exhaustive research and extensive interviews with key financial insiders, politicians, journalists, and academics, this film traces the rise of a rogue industry which has corrupted politics, regulation, and academia.